The effects of tualang honey on bone mineral density as an adjuvant therapy to anastrozole among postmenopausal breast cancer patients - Hassan, Nor Hasnina Mohd (2016)
Objective: To determine the effects of Tualang Honey (TH) on bone mineral density (BMD) as assessed by dual energy X-ray absorptiometry (DEXA) scan when used as an adjunct to anastrazole among postmenopausal breast cancer patients. Methodology: Patients (n=33) were recruited from the Oncology Clinic, Hospital USM, Kelantan, Malaysia. The inclusion criteria included postmenopausal women with breast cancer stages I, II, or III, oestrogen receptor (ER) positive and/or progesterone receptor (PgR) positive. The patients were randomized to receive either anastrozole (1 mg) alone or anastrazole (1 mg) and TH (20 g) intervention group. Bone DEXA scan was conducted twice, at baseline (during the first visit) and six months later. Results: The T scores were significantly decreased when compared to the baseline for both femoral (−0.40 vs −0.50, p = 0.013) and the lumbar spine (−1.60 vs –1.70, p = 0.034), following six months of anastrozole alone treatment. On the other hand, there was no significant difference between the baseline and the T scores following six months of treatment for both femoral (0.35 vs. 0.50, p = 0.286) and the lumbar spine (−1.05 vs –0.95, p = 0.074) for the intervention group indicating that TH can ameliorate bone loss as a resultof anastrazole use. Administration of anastrozole significantly reduced the median femoral BMD by 2.23% and median lumbar spinal BMD by 2.84% after six months. However, in the intervention group, there was no significant change in term of both BMD and T score when compared to the baseline following six months which again indicate the potential of TH in ameliorating bone loss. Conclusions: TH has the potential to be used as an adjunct to prevent bone loss among postmenopausal breast cancer women treated with anastrozole